Power, polarity, and prudence: the ambiguities and implications of UK discourse on a multipolar international system. Issue 3 (3rd July 2019) - Blagden, David
ABSTRACT: What do UK policymakers mean when they say that Britain's strategic environment is returning to "multipolarity"? In realist international theory, polarity is a specific causal concept; the number of powers capable of balancing even the most capable other state(s) in the international system ("poles") is taken to determine the system's stability. Does the post-2017 appearance of polarity references in British security policy documents therefore reflect some unexpected UK renaissance of realist thought? Or is something else going on, as recent work by Ben Zala suggests? This article will demonstrate that, while UK official usage of the "multip–" word has indeed flourished recently, the term is actually being used in a more elastic, less bounded way than realism prescribes in order to generate other kinds of political effect. Specifically, "polarity" (and its "multi-" prefix) is used to characterise the behaviour of those major states that oppose Western-preferred international order, to elide Britain's own relative power/status tensions, and to capture an expansive laundry-list of perceived international dangers. The article then discusses five ways in which a shift in polarity could negatively affect Britain; important consequences that merit preparatory contemplation, yet that an imprecise, catch-all understanding of "multipolarity" too readily obscures.